Shivani Sivagurunathan, What Has Happened to Harry Pillai?: Two Novellas. Penang: Clarity Publishing, 2022. 267 pp. ISBN 978-967-17657-8-4.: Book Review - Samarawickrama, Enakshi (SARE: Southeast Asian Review of English, 2023)
None